The distribution of IgG subclasses in the lupus band suggests disease-specific alteration in subclass switching rather than polyclonal B-cell activation. - Alahlafi, A; Wordsworth, P; Wojnarowska, F (2004)
Deposition of immunoglobulins in the skin of patients with lupus erythematosus (LE), demonstrable as a linear band 'lupus band' at the basement membrane zone (BMZ) by direct immunofluorescence, was first described in 1963. Four decades after the discovery of the lupus band, a basic question regarding the origin of immunoglobulins of the lupus band is still unanswered. Is the lupus band just a manifestation of polyclonal B-cell activation commonly seen in systemic LE (SLE)? The distribution of IgG subclasses deposited in the skin of patients with SLE was identified using immunohistochemistry. The relative restriction of IgG of the lupus band to the IgG3 subclass demonstrated in this study provides evidence against polyclonal B-cell activation as the only cause of the lupus band and suggests disease-specific alteration in subclass switching.